Red Sugar - Beatty, Jan, 1952- (Book collections on Project MUSE., 2008)
"Red Sugar is tantalizing and forbidden, but it is no peepshow. The poems are raw, brash, and full of pluck, yet there is tenderness and honest emotion at the core. Jan Beatty reminds us that there is 'nothing / between us and death but one inch.' She takes us to the edge of being and shows us our own quick mortal souls. Yes, there's rock music and prison sex-but do not think for a moment that this book is merely licentious. Beatty casts a broad canopy over human desire, and within the scope of experience, she finds, too, that we are innocent and sublime beings. A rich, rare treat, this Red S